Dual-Mode Single-Input Three-Output Multifunction Filter and Quadrature Oscillator Consisting of Two Voltage Differencing Transconductance Amplifiers and Two Grounded Capacitors - Tangsrirat, W.; Channumsin, O.; Unhavanich, S.; Pukkalanun, T. (My University, 2023)
Abstract: In this paper, we present the circuit configuration that can perform as a dual-mode (i.e., both voltage-mode and current-mode) multifunction filter as well as a dual-mode quadrature oscillator by slightly modifying the design. The presented configuration includes only two voltage differencing transconductance amplifiers and two grounded capacitors, resulting in a resistor-less construction. The dual-mode multifunction filter with one input and three outputs provides three standard biquadratic filter functions: highpass, bandpass, and lowpass, as well as independent electronic adjustment of its quality factor. The circuit can also be used to implement a dual-mode quadrature oscillator with orthogonal electronic control of the oscillation condition and the oscillation frequency. Simulation results based on 0.25-μm level-7 TSMC CMOS technology parameters are used to evaluate the behavior of the proposed dual-mode multifunction biquad and quadrature oscillator circuit.
Keywords: dual-mode; multifunction filter; quadrature oscillator; resistor-less circuit; Voltage Differencing Transconductance Amplifier (VDTA)